2021
DOI: 10.3390/molecules26051354
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Metabolism of Methyltestosterone and Metandienone: Detection of Novel A-Ring Reduced Metabolites

Abstract: Metandienone and methyltestosterone are orally active anabolic-androgenic steroids with a 17α-methyl structure that are prohibited in sports but are frequently detected in anti-doping analysis. Following the previously reported detection of long-term metabolites with a 17ξ-hydroxymethyl-17ξ-methyl-18-nor-5ξ-androst-13-en-3ξ-ol structure in the chlorinated metandienone analog dehydrochloromethyltestosterone (“oral turinabol”), in this study we investigated the formation of similar metabolites of metandienone an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
2
12
2
Order By: Relevance
“…After the comparison of the retention time and mass spectra from analyte 1 with reference materials, analyte 1 was identified as 17β-hydroxy-17α-methyl-5β-androst-1-en-3-one ( M4 , RT 3.987 min). This is also in accordance with the results published before (Schänzer 1996 ; Loke et al 2021 ), which report that almost all of the reduced metabolites produced from MD show the 5β-stereochemistry structure.
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…After the comparison of the retention time and mass spectra from analyte 1 with reference materials, analyte 1 was identified as 17β-hydroxy-17α-methyl-5β-androst-1-en-3-one ( M4 , RT 3.987 min). This is also in accordance with the results published before (Schänzer 1996 ; Loke et al 2021 ), which report that almost all of the reduced metabolites produced from MD show the 5β-stereochemistry structure.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Although its clinical approval was withdrawn in the early 1980s, metandienone is still marketed and used for performance enhancement. The metabolism of the orally bioavailable metandienone has been investigated thoroughly for decades, and there is still interest in finding new metabolites which might contribute to an elongation of the detection window (MacDonald et al 1971 ; Schänzer et al 1991 , 2006 ; Pozo et al 2009a ; Loke et al 2021 ; Parr et al 2012 ). The most obvious way to study human xenobiotic metabolism is the administration to volunteers and the collection of their urine.…”
Section: Introductionmentioning
confidence: 99%
“…As the metabolism of metandienone has been thoroughly studied over the past decades, we chose this AAS to investigate the usability of HepG2 cells as model substance to study long-term metabolism. 25,27,28,[46][47][48] Our results show that the cells possess the enzymatic pattern requisite for the formation of metandienone metabolites including its long-term metabolites, for which sequential reactions are necessary. The phase II metabolites formed by HepG2 (glucuronide-and sulfo-conjugated) are also in accordance to that detected in human urine samples.…”
Section: Metandienone Metabolismmentioning
confidence: 65%
“…Additionally, work conducted using LC–MS pointed towards the added benefit of including 17α‐hydroxy‐17β‐methyl‐androst‐4,6‐dien‐3‐one (4,6‐dien‐17epi‐MT) that is excreted unconjugated (free) 27 . Attempts were made to find the metabolite reported by Loke et al, 37 but they were unsuccessful. However, publication by Schänzer et al 38 reported the 17‐epimer versions of 5α‐MT and 5β‐MT after hydrolysis, which were successfully determined in excretion urine for this study.…”
Section: Resultsmentioning
confidence: 99%